PENGARUH LINGKUNGAN KERJA, INSENTIF, PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA UKM ROTI DI SAYUNG DEMAK - Rahmawati, Indah; Indriasari, Ika; Violinda, Qristin (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to determine the effect of work environment, incentives, work experience on employee productivity at UKM Roti in Sayung Demak. The population of researchers is all employees who work in UKM Roti in Sayung Demak, the sample that has been determined in this study amounted to 61 respondents using non probability sampling with saturated sampling technique method (census). Data analysis in this study using the SPSS 24 program. Hypothesis testing with multiple linear regression approaches. The results of the analysis and discussion show that the variables have a persial effect, namely; Work Environment has a positive and significant effect on Work Productivity, Incentives have a positive and significant effect on Work Productivity, and Work Experience has a positive and significant effect on Employee Productivity at UKM Roti in Sayung Demak.